Progressive Business Models Creating Sustainable and Pro-Social Enterprise (Palgrave Studies in Sustainable Business In Association with Future Earth,, 2018)
This book presents and analyses exemplary cases of progressive business, understood as ecologically sustainable, future-respecting and pro-social enterprise. The authors present a number of companies following progressive business practices from a range of industries including ethical and sustainable banking, artisan coffee production and distribution, pharmaceutical products, clean technology, governance in retailing, responsible hospitality and consumer goods. With case studies from around Europe such as Tridos Bank in The Netherlands, Béres Co. in Hungary, Novo Nordisk in Denmark, Lumituuli in Finland, John Lewis in the UK and Illy Café from Italy, these progressive companies have global reach and an international impact. The collected cases aim to show the best to be expected from business in the 21st century in a structured accessible way, suitable for any readers interested in innovative ways of creating forward-looking sustainable business.